Penggunaan Antibiotik Profilaksis Pada Pembedahan Terbuka Batu Saluran Kemih Di RSUD Arifin Ahmad Provinsi Riau - Dimas Pramita Nugraha; Dina Fauzia; M.Yulis Hamidy; M.Irvan Noorrahman (Fakultas Kedokteran Universitas Riau, 2016)
Open surgery urinary tract stones are classified as clean-contaminated surgerywheresurgical prophylactic antibioticsare recommended.The purpose of this study was to determine the pattern and correct use of surgical prophylacticantibiotic in patients undergoing open surgery urinary tract stones in Arifin Ahmad Hospital.This research is a descriptivestudy using secondary data from medical records of patients who underwent open surgery urinary tract stones, with atotal sample amounted to 82 people. The precision of the use of antibiotics assessed based PermenkesGuidelines Useof Antibiotics.The results showed the use of prophylactic antibiotics for urinary tract surgery have not been preciselyclassified according to the indication the use of antibiotics andthe timing of antibiotics.Even though the durationantibiotics, dosage, and route of administration of prophylactic antibiotics are appropriate under the guidelines.Theuse of prophylactic antibiotics for open surgery urinary tract stones need improvement.